What makes a food healthy? Sex differences in what is associated to healthiness evaluations. (March 2022) - Foroni, Francesco; Esmaeilikia, Mahsa; Rumiati, Raffaella I.
Highlights: Different dimensions are associated to healthiness evaluation of high-calorie food in males and females. Valence and perceived calorie content are associated to healthiness of low-calorie food. In females the more hedonic pleasing a food is, the least healthy is evaluated. Abstract: Food healthiness evaluations are important precursors of food choices as health beliefs guide a large portion of our food intake. In the present study we investigated the healthiness evaluations of males and females and the extent to which valence, arousal, familiarity, hedonic value, and perceived calorie are associated to the healthiness attributed to different food. Ninety-two healthy normal-weight adults evaluated Low-Calorie foods (e.g., salad) and high-calorie foods (e.g., chips) on valence, arousal, familiarity, hedonic value, perceived calorie content, and healthiness. For both females and males, valence and perceived calorie content are associated with healthiness ratings of low-calorie food as well as with high-calorie food. The more positive and less caloric is considered a food, the more is considered healthy. These are the only dimensions linked to healthiness ratings of low-calorie foods. Instead, high-calorie food healthiness is also associated to its arousal and hedonic value for females while to its familiarity for males. These results highlight key dimensions related to how healthy a food is considered by lay persons. Moreover, they show that different dimensions are associated to healthiness of a food for females and males. Even though there are dimensions associated to healthiness evaluation irrespective of the sex and of the type of food (i.e., valence, perceived calorie content), other dimensions relate only to high-calorie food and are relevant either for females (arousal, hedonic value) or for males (familiarity). Thus, different dimensions could be leveraged to develop sex-targeted interventions depending on the type of food.